Judicial activism as constitutional panacea: An appraisal - Dey, Bata K. (1999)
With a backdrop of perspectives on Constitutional Provisions to facilitate conceptual clarity on judicial activism, the author embarks on a detailed appraisal of PIL embodying judicial activism as a much-needed Constitutional panacea, in its unfailing form of judicial assertiveness to secure justice, liberty, and equality for all. He analytically examines its nature, areas of operation, justification, necessity in view of variance in judges' competence to deliver justice, charges of its transgression in the domains of Legislature and Judiciary, its relationship with court's contempt provision, its objectives of realising social justice and enhancing poorman's access to justice as a matter of right, drawing vital support from its achievements. Thus, putting up a strong defence for judicial activism, he concludes alleying apprehensions of its critics. - Reproduced
Keywords: Judiciary